Proses Kreatif Penciptaan Tari Wong Peken oleh Jasmine Okubo - Gayatri, Ni Komang Ananda; Kustiyanti, Dyah; Sudibya, I Gusti Ngurah (Jurnal IGEL : Journal Of Dance, 2021)
This article is the result of research into the creative process of creating Wong Peken dance as a contemporary dance that was specifically created for the deaf. This research is focused on how the creativity process is carried out by Jasmine Okubo as the choreographer. Indirectly, this dance breaks the stigma of the people who underestimate the deaf because it has managed to get a fairly good appreciation. Interestingly, Jasmine Okubo has no background or experience in BISINDO communication. The method applied in this research is a qualitative method with reference to the Theory of Creativity. The results obtained indicate that the process of creating Wong Peken dance is a process of the body's journey to find the specialties in each individual regardless of their imperfections. The process of creating Wong Peken dance shows that dance is a universal language for expression and communication. Dance allows people who cannot speak to communicate through movements.Keywords : Wong Peken Dance, creative process, deaf.